Malaysian SILN Students’ Difficulties in Statistical Understanding and Mathematical Communication - Harjati, Juliana Kristin; Usodo, Budi; Nurhasanah, Farida (EDUPEDIA Publisher, 2025)
Purpose -Indonesian children abroad, including those in Malaysia, are entitled to quality education through Sekolah Indonesia Luar Negeri (SILN). However, the existence of schools alone is insufficient. This study explores students' difficulties in learning statistics, focusing on mathematical communication within a multilingual learning environment. Methodology - Using a qualitative descriptive design, the study involved two mathematics teachers and 32 students selected via purposive sampling from an Indonesian school in Malaysia. Data were collected through in-depth interviews (Zoom) and mathematical communication tests (WhatsApp)—analysis employed cross-comparison techniques, aligning teacher responses with student test results based on predefined communication indicators. Findings - Three main difficulties emerged: (1) student errors in multi-digit statistical computation and representation, (2) instructional challenges due to teachers' limited background in mathematics education, and (3) language barriers stemming from the use of Malay in daily life and Indonesian in instruction, impacting comprehension and expression in mathematical contexts. Novelty - This study uniquely connects statistical learning challenges with cross-linguistic dynamics and mathematical communication in an overseas Indonesian school context. Significance - Findings provide insights for educators, curriculum developers, and policymakers to enhance statistical instruction and communication skills in multilingual settings, contributing to improved educational quality for Indonesian students abroad.